Margaret Atwood's Hag-Seed: The Aesthetics of Retelling Shakespeare's The Tempest. - Klooß, Wolfgang (University of Toronto Quarterly, 2023)
Comparing Hag-Seed with The Tempest, this article tries to disclose how Margaret Atwood shifts and extends perspectives in her novel by empowering the female voice in Hag-Seed. In contrast to Shakespeare's original and many of its postcolonial successors, the latter of which have sustainably promoted a political reading of the Bard's play, Hag-Seed, for instance, offers a treatment of Miranda that reverses the role of Prospero's daughter from a passive to an influential "active" character who has a decisive say in many of her father's doings. In a similar vein, other female voices in the novel come to the fore. These observations are accompanied by brief intertextual references to a painting by William Hogarth, created circa 1736, and Peter Greenaway's film Prospero's Books, released in 1991. The article shows how aesthetic forms of expression and political rhetoric are interlinked, especially how aesthetic and (gender-)political values interplay.